Assessment of the Range of Motion in Adhesive Capsulitis of Shoulder Joints in Type 2 Diabetic Patients - Sharif, Rayhan; Alam, Shamina; Islam, S M Mazharul (Eastern Medical College Journal, 2025)
Background: Adhesive capsulitis is a condition characterized by pain and restricted range of motion (ROM) in the shoulder joint. Type 2 diabetes mellitus has been associated with an increased incidence of adhesive capsulitis, potentially exacerbating shoulder dysfunction. The objective of this study is to assess the ROM in the shoulder joints of patients with adhesive capsulitis and type 2 diabetes mellitus. Materials and methods: This cross-sectional observational study was carried out in the outpatient department of Physical Medicine and Rehabilitation, Dhaka Medical College and Hospital (DMCH), Dhaka from July 2021 to June 2022. A total of 122 diabetic patients with adhesive capsulitis attending the study place were selected by purposive sampling. Patients with a history of trauma, surgery, neurological conditions affecting shoulder, rheumatoid arthritis, thyroid disorders, pain or disorders of cervical spine, elbow, wrist or hand and rotator cuff rupture and tendon calcification were excluded from the study. The patient’s pain was recorded using the visual analogue scale (VAS). Movements of the affected shoulder joint were measured by using a goniometer. The validated Bangla version of Shoulder Pain and Disability Index (SPADI) was used to assess functional status. Variables were expressed as mean ± standard deviation (SD), frequency and percentage. Results: The mean age of the patients was 51.9 ± 8.6 years. In this study 74 patients (61%) had adhesive capsulitis on their right shoulder and the rest 48 (39%) had adhesive capsulitis on their left shoulder. The mean flexion, extension, abduction, internal rotation and external rotation was 99.9±20.2, 39.5±11.7, 94.9±20.3, 34.7±15.0 and 53.7±12.6 respectively. There was a significant positive correlation between blood glucose level and pain score in VAS and SPADI. However, there was no significant correlation between blood glucose level and range of motion of patients. There was no significant correlation between duration of diabetes and pain, range of motion and functional impairment of patients in this study. Conclusion: Adhesive capsulitis in Type 2 diabetic patients is associated with greater limitations in shoulder range of motion. Poor glycemic control might exacerbate the severity of shoulder dysfunction, highlighting the importance of managing blood sugar levels in this patient to prevent further mobility impairment. Eastern Med Coll J. July 2025; 10 (1): 76-80